Larangan Logo dan Simbolik LGBT pada Piala Dunia 2022 di Qatar Menurut Fiqh Siyasah dan Hubungan Internasional - Pratiwi, Nur Rizky; Irwansyah, Irwansyah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of this study is to discuss the prohibition of LGBT in the World Cup. As one of the developed countries in the Middle East, of course Qatar is considered as one of the countries that has great influence in solving various problems in the global arena. Including their appearance at the 2022 World Cup. This World Series is very special because this is the first time this tournament has been held in the Middle East region. A thing that is quite rare considering the world of football is more inclined to European and Latin American football civilizations. The 2022 World Cup is going quite well, but controversial issues remain. The crux of the problem is that the state of Qatar prohibits LGBT attributes, which has led to harsh criticism from countries with their own understanding of LGBT. The research method used to solve this problem is normative law, and data is collected through primary data and analyzed qualitatively. This study claims that Qatar, which was chosen to host the World Cup, has the right to decide on several regulations according to the laws of the country. This has become FIFA's official rules as the organizer of the World Cup. One of Qatar's rules is to prohibit LGBT campaigns that violate Islamic religious law.